Injection of ROS‐Responsive Hydrogel Loaded with Basic Fibroblast Growth Factor into the Pericardial Cavity for Heart Repair - Li, Zhenhua; Zhu, Dashuai; Hui, Qi; Bi, Jianing; Yu, Bingjie; Huang, Zhen; Hu, Shiqi; Wang, Zhenzhen; Caranasos, Thomas; Rossi, Joseph; Li, Xiaokun; Cheng, Ke; et al. (Advanced functional materials, 2021)
Myocardial infarction, among other ischemic heart diseases, is the major cause of mortality and morbidity for patients who have heart diseases. Timely reperfusion of the ischemic myocardium is the most effective way to treat myocardial infarction. However, blood reperfusion to the ischemic tissues leads to an overproduction of toxic reactive oxygen species (ROS), which can further exacerbate myocardial damage on top of ischemic injury. ROS has been used as a diagnostic marker and therapeutic target for ischemia‐reperfusion (I/R) injury and as an environmental stimulus to trigger drug release. In this study, a ROS‐sensitive cross‐linked poly(vinyl alcohol) (PVA) hydrogel is synthesized to deliver basic fibroblast growth factor (bFGF) for myocardial repair. The therapeutic gel is injected into the pericardial cavity. Upon delivery, the hydrogel spread on the surface of the heart and form an epicardiac patch in situ. In a rat model of I/R injury, bFGF released from the gel could penetrate the myocardium. Such intervention protects cardiac function and reduces fibrosis in the post‐I/R heart, with enhanced angiomyogenesis. Furthermore, the safety and feasibility of minimally invasive injection and access into the pericardial cavity in both pigs and human patients are demonstrated. Fibroblast growth factor (FGF)‐based therapeutics have been widely studied and are currently under investigation in several clinical trials. However, delivery of FGF to the heart is challenging. Moreover, controlled release by injury biomarkers is desirable. Here, a FGF‐loaded and reactive oxygen species‐responsive hydrogel for intrapericardial delivery is fabricated. Furthermore, safety and feasibility of minimally invasive intrapericardial injection (access) in pigs and a human patient are tested.